2014
DOI: 10.1596/1813-9450-6905
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Border Mergers and Acquisitions in Services: The Role of Policy and Industrial Structure

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
5
1
1
Order By: Relevance
“…As with distance, this effect of ethnic networks may signal the importance of cultural sensitivity in delivering many types of services, such as hospitality, retail, education, and medical services. This result is in line with research that finds that cultural distance is more relevant for mergers and acquisitions in services (Barattieri, Borchert, and Mattoo 2016).…”
Section: Networked Firms Are More Likely To Invest Making Investing More Inclusivesupporting
confidence: 91%
“…As with distance, this effect of ethnic networks may signal the importance of cultural sensitivity in delivering many types of services, such as hospitality, retail, education, and medical services. This result is in line with research that finds that cultural distance is more relevant for mergers and acquisitions in services (Barattieri, Borchert, and Mattoo 2016).…”
Section: Networked Firms Are More Likely To Invest Making Investing More Inclusivesupporting
confidence: 91%
“…Furthermore, we controlled for two dyadic factors. First, we captured commonality in religion between the two countries (Barattieri, Borchert, & Mattoo, ). Using data from Alesina et al (), we identified common religions practiced in both countries, multiplied proportions of the populations for the acquiring and target country practicing a given common religion, and summed the products for all common religions to derive a measure of the degree of common religion.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we controlled for two dyadic factors. First, we captured commonality in religion between the two countries (Barattieri, Borchert, & Mattoo, 2014). Using data from Alesina et al (2003), we identified common religions practiced in both countries, multiplied proportions of 11 South Africa was administered as a settlement colony and became independent in 1910 when the Union of South Africa was formed, almost 50 years before other African countries began to gain independence.…”
Section: Control Variablesmentioning
confidence: 99%
“…In our case, the country variability being particularly important, we adopt an alternative twostep method, initially developed by Saxonhouse (1976) and eventually refined by several authors such as Woolridge ( 2010), Hornstein and Greene (2012) or Bryan and Jenkins (2016), and implemented in various empirical studies (Hug and Spörri, 2011;Barattieri et al, 2016).…”
Section: The Econometric Strategy: a Two-step Approachmentioning
confidence: 99%